Соціальне житло в системі соціального захисту та відтворення трудового потенціалу населення України - Пожуєва, Т.О. (Економічний вісник Донбасу, 2025)
Масштабні руйнування житлового фонду України внаслідок воєнної агресії зумовили нову хвилю наукових дискусій щодо ролі соціального житла в системі соціального захисту та відтворення трудового потенціалу. Проблематика набуває особливого значення у зв’язку з масовим внутрішнім переміщенням населення, ризиком довгострокових демографічних втрат та зростанням нерівності на ринку праці. Водночас житло розглядається не лише як гуманітарний ресурс, а як стратегічний чинник формування економічної безпеки, що впливає на зайнятість, здоров’я та продуктивність працівників, а також на регіональний розвиток у післявоєнний період. The large-scale destruction of Ukraine's housing stock as a result of military aggression has sparked a new wave of scientific debate on the role of social housing. This role has manifested itself in the system of social protection and reproduction of labor potential. The current issues are particularly important in connection with the mass internal displacement of the population, the risk of long-term demographic losses, and growing inequality in the labor market. At the same time, housing is seen not only as a humanitarian resource, but also as a strategic factor in shaping economic security. This factor affects employment, health, worker productivity, and regional development in the post-war period. The aim of the study is to provide a theoretical and practical justification for the mechanism of providing social housing as a component of the social protection system and the reproduction of labor potential in wartime and post-war conditions. The objectives of the article are to identify current trends in the development of social housing in Ukraine and its impact on employment and productivity. The authors also set themselves the task of describing innovative management models and developing concepts for housing clusters as a new tool for regional recovery. The methodological basis was provided by systemic and structural-functional approaches. This allowed social housing to be considered as an element of a complex socio-economic system. The publication uses comparative analysis methods to compare Ukrainian and European practices, statistical analysis to identify the scale of losses and assess restoration needs. The authors used graphical visualization to build models and diagrams of housing clusters. The results of the study showed that social housing in Ukraine is transforming from an auxiliary tool of social policy into a key element of the strategy for restoring labor potential. It has been established that the quality of housing conditions directly affects the physical and mental health of the population, stress levels, family stability, and the integration of displaced persons into communities, which ultimately determines labor productivity. It has been substantiated that the restoration of the housing stock has a multiplier effect, contributing to the revitalization of the construction sector, related industries, and local labor markets. A concept of housing clusters has been proposed, with social housing at its core. Infrastructure, entrepreneurship, and communities are formed around this core. This, in turn, ensures long-term socio-economic stability. The scientific novelty of the study lies in the interpretation of social housing as a multifunctional tool: it is not only social protection, but also a catalyst for the restoration of labor potential, demographic stabilization, and regional development. For the first time, a model of housing clusters has been proposed that integrates housing, social services, business infrastructure, and digital services into a single ecosystem. The practical significance of the results obtained lies in the possibility of their application for the formation of state and regional programs for the reconstruction of the housing sector, the integration of social protection policy with employment policy, Thus, the results obtained contribute to the adaptation of best European practices to Ukrainian realities. The proposed approaches are capable of not only meeting the basic needs of the population, but also contributing to the sustainable economic development of Ukraine in the long term.